Characterization of critical flux of a submerged MBR system - Ng, Pei Ing. (2009)
This dissertation describes the characterization of critical and limiting flux in submerged membrane bioreactor (MBR) system. Two important concepts which are the existence of limiting flux and critical flux were well studied in the current research. Besides that, the complex mechanism of membrane fouling which resulted in the flux reduction is also included in this thesis. Rapid batch-scale membrane filtration tests were carried out for the determination of limiting and critical flux. Limiting flux test was conducted under constant pressure while pressure stepping with time interval of 3, 6, 12 and 36 minutes was carried out in the critical flux test. The relationship between critical and limiting flux was further drawn in this thesis. For a given membrane under a feedwater composition, increasing pressure resulted in increased flux reduction. A limiting flux seemed to exist beyond which, membrane flux cannot be sustained. Membranes with initial flux higher than the limiting flux underwent fouling and the pseudo stable flux approached the limiting flux. Flux reduction was insignificant if the initial flux was lower than the limiting flux. Furthermore, limiting flux seemed to be membrane independent but greatly dependent on feedwater composition such as pH value and crossflow velocity. Besides that, the initial flux of mixed liquor was lowered than the pure water flux. This could be caused by concentration polarization or rapid membrane fouling during the initial stage of filtration. Under pressure stepping method, a strong dependence of critical flux on the timescale was observed. The degree of membrane fouling was mainly controlled by the filtration’s timescale. A strong relationship between critical and limiting flux was observed in current investigation. The optimum time taken in the determination of critical flux was found to be greater than specific limiting time, τ. Membrane fouling causes increased cost and energy consumption during filtration process. Thus it is advisable to operate the plant at sustainable flux where the permeability and selectivity of membrane is optimum, and the fouling rate is at acceptable range. Moreover, sustainable flux operation requires lower cost and energy consumption.